O Teatro em cuidado de si: práticas de autoconhecimento na vivências de um corpo ansioso - LINHARES, Amanda de Mendonça (2022)
This monograph focuses on a subject entitled O Teatro em Cuidado de Si: Práticas de Autoconhecimento nas Vivências De um Corpo Ansioso. This is narrated my own body’s trajectory in a context of its personal and collective experiences, whether or not facing conflicts related to anxiety disorders. It was indeed subjecting me to experiences that I could achieve results which might be translated into proposals to groups, to be used in scenes, games or performances; all this being sought in the context of an anxious’ experimental trajectory, unlike it could usually be expected from bodies at scene. As much as like entangled (though interconnected) facts, in a rizhome, I sought to keep in each chapter the main monograph’s purpose which is exploring (new) “territories”. Altogether this monograph comprises three parts including: my personal experiences, in the Floreat Ministry, and with the University Theatre Team called “Mulher em Cuidado de Si”. When preparing this monograph my main source of information was represented by the authors: Gilberto Icle, Jean Vanier, and Viola Spolin